TRIPLE BOTTOM LINE APPROACH FOR EVALUATING EFFICIENCY AND RESILIENCE OF NATIVE CHICKEN FARMING: CASE STUDY IN MEDAN CITY - Tampe Tuah Malem Ginting; Arief Muhazir Insandi; Surya Sevi Wijayana Lumban Tobing (RADJA PUBLIKA, 2025)
This study applies the Triple Bottom Line (TBL) framework to comprehensively evaluate the efficiency and resilience of native chicken farming enterprises in Medan City, Indonesia. The research employed a mixed-methods approach by combining quantitative and qualitative data. Primary data were obtained from 30 farmers through structured surveys and in-depth interviews, while secondary information was collected from official reports and relevant literature. Economic efficiency was measured using Stochastic Frontier Analysis (SFA), and social as well as environmental dimensions were assessed through descriptive and qualitative analysis. The findings reveal that the average technical efficiency (TE) of the farmers is 0.72, allocative efficiency (AE) is 0.68, and economic efficiency (EE) is 0.65, indicating that nearly 75% of the sampled farmers remain economically inefficient. Socially, native chicken farming contributes to household income diversification, employment opportunities, and local food security, but constraints persist in the areas of farmer capacity development, access to markets, and institutional support. Environmentally, waste management practices are still limited, with inadequate utilization of by-products, potentially threatening ecological sustainability in the long run. These results emphasize that strengthening economic efficiency alone is insufficient; it must be aligned with social empowerment and ecological responsibility to enhance overall resilience. The study contributes practical insights for policymakers, farmer associations, and stakeholders in designing targeted interventions to increase competitiveness and long-term sustainability of native chicken farming under dynamic economic conditions.